Are effects of COVID-19 pandemic on financial markets permanent or temporary? Evidence from gold, oil and stock markets. (June 2022) - Tuna, Gülfen; Tuna, Vedat Ender
Abstract: The purpose of this study is to examine the effect of COVID-19 pandemic on gold, oil, conventional and Islamic stock markets. Two variables as the number of new COVID-19 cases and Infectious Disease Equity Market Volatility (IDEMV) Index developed by Baker, Bloom, Davis and Kost (2019) are used in order to discuss the effect of COVID-19 pandemic. Other variables used in the research are oil prices, gold prices and S&P Dow Jones Index values for conventional and Islamic stock markets. The data set used in the study is the daily data set between 31st December 2019 and 5th May 2020 for all variables. Time and frequency domain causality test is used in the study. According to the study results, there is a permanent causality in long term between stock markets, gold and oil prices and the number of COVID-19 cases. There is also a permanent causality in long term between IDEMV and gold and oil prices. However, in short term, there is a temporary causality between gold and oil prices and the number of COVID-19 cases. These results are highly important especially for policy performers and portfolio managers to determine the portfolio strategies. Highlights: The effect of COVID-19 Pandemic on gold, oil and stock markets is analyzed. There is a permanent causality between stock markets, gold and oil prices and the number of COVID-19 cases in long term. There is a temporary causality between gold and oil prices and the number of COVID-19 cases in short term.